Jan Driessen and Alessandro Vanzetti (eds), Communication Uneven. Acceptance of and Resistance to Foreign Influences in the Connected Ancient Mediterranean. Aegis 20. - Alvarez, Laura (Journal of Greek Archaeology, 2022)
Jan Driessen and Alessandro Vanzetti (eds), Communication Uneven. Acceptance of and Resistance to Foreign Influences in the Connected Ancient Mediterranean. Aegis 20. pp. 210, with col. and b/w ills, maps and tbls. Louvain-la-Neuve: Presses Universitaires de Louvain, 2020. ISBN 978-2-39061-087-8, paperback €32.50.